Influence of dry extract of brassica olearacea on the morphological structure of the gastric mucosa of rats during an experimental ulcer caused by alcohol-prednisolone mixture - Kononenko, Nadiia; Mirzaliev, Mirzachan; Chikitkina, Valentina (ScienceRise: Pharmaceutical Science, 2019)
Aim – study of the effect of cabbage dry extract on the morphological state of the gastric mucosa of rats on the background of an experimental alcohol-prednisolone ulcerative lesion. Materials and methods. Ulcerative lesions of the gastric mucosa of nonlinear white rats were reproduced by intragastric administration of a mixture of 80% ethanol and prednisolone 20 mg/kg at the rate of 0.6 ml per 100 g of body weight. Dry extract of cabbage in doses of 30, 40, 50 and 60 mg/kg and the reference drug Altan at a dose of 1 mg/kg was administered intragastrically in the treatment and prophylactic mode: daily for 3 days before pathology simulation, on the day of the introduction of the alcohol-prednisolone mixture and the next day at the end of the experiment. Histologically we examined the mucous membrane of the fundus and pyloric stomach. Conducted semi-quantitative assessment of the mucous membrane by the presence of destructive changes within the entire microdrug, haemocapillar disorders, edema of mucosal stroma and productivity of mucoid secretion by mucous-forming cells of the pathogenic epithelium outside the destructive zones by the intensity of the periodic acid Schiff reaction. Results. The introduction of an alcohol-prednisolone mixture to rats led to the emergence of a pronounced acute ulcer-erosive process in various parts of the gastric mucosa, which was accompanied by significant hemocapillary disorders and stromal edema. In most cases, the ulcers spread to the entire depth or most of the glandular tubes. In areas outside the zones of destruction, a decrease in mucoid secretion by cells of the gastric superficial-foveolar epithelium, additional cells of its own glands, glandular cells of the pyloric glands, stimulation of pepsin production, increased acid formation were observed. Dry extract of cabbage reduced the severity of acute ulcerative-erosive process and hemocapillary disorders and edema, restriction of degradation zones occurred, processes of mucoid synthesis stabilized, severity of pepsin and acid formation decreased. The experimental data indicate pronounced gastroprotective properties of dry extract of cabbage, the most pronounced positive effect is set at a dose of 50 mg/kg Conclusions. According to the activity of the gastroprotective effect of dry extract of cabbage, it prevailed in comparison with the domestic plant-based drug Altan at a dose of 1 mg / kg. The results indicate the promise of further experimental studies of the pharmacological properties of dry extract of cabbage in order to create an effective anti-ulcer phytopreparation